STAT3 inhibition ameliorates renal interstitial inflammation in MRL/lpr mice with diffuse proliferative lupus nephritis - Jianfen Zhu; Yijing Chen; Yulan Chen; Yinqiu Lv; Tianxin Chen (Renal Failure)
Background and objectives Acute kidney injury (AKI) is one of the most common and severe clinical syndromes of diffuse proliferative lupus nephritis (DPLN), of which poor prognosis is indicated by aggravated renal function deterioration. However, the specific therapy and mechanisms of AKI in DPLN remain to be explored.Methods The correlation between AKI and clinical pathological changes in DPLN patients was analyzed. Expression of STAT3 signaling was detected in MRL/lpr mice with DPLN using immunohistochemical staining and immunoblotting. Inhibition of STAT3 activation by combination therapy was assessed in MRL/lpr mice.Results Correlation analysis revealed only the interstitial leukocytes were significantly related to AKI in endocapillary DPLN patients. MRL/lpr mice treated with vehicle, which can recapitulate renal damages of DPLN patients, showed upregulation of STAT3, pSTAT3 and caspase-1 in renal cortex. FLLL32 combined with methylprednisolone therapy significantly inhibited the STAT3 activation, improved acute kidney damage, reduced the interstitial infiltration of inflammatory cells and decreased the AKI incidence in MRL/lpr mice.Conclusion STAT3 activation may play an important role in the pathogenesis of DPLN and the development of AKI. Hence, STAT3 inhibition based on the combination of FLLL32 with methylprednisolone may represent a new strategy for treatment of DPLN with AKI.